Organo-functionalized polyoxovanadates: crystal architecture and property aspects - Wang, Jilei; Liu, Xiaomei; Du, Zeyu; Xu, Yan (Dalton transactions : an international journal of inorganic chemistry, 2021)
Polyoxovanadates (POVs), as one of the most prominent members of polyoxometalates (POMs), have been subject to extensive studies by virtue of their aesthetically intriguing structures and potential applications in catalysis, magnetism, and optics, among others. In recent years, organo-functionalized POVs have received considerable attention due to the combination of the advantages of POVs with the importance of organic species. In this review, the key developments of polyoxovanadates and, particularly, the achievements that are related to polyoxovanadates modified with organic ligands and transition metal-organic ligand are summarized. Herein, we systematically introduce the structural features of organo-functionalized POVs and their main applications involved in the magnetism and catalysis aspects. Finally, the current challenges and future prospects in the design, synthesis, and property investigation of polyoxovanadates are also discussed. The latest progress on polyoxovanadates modified with organic ligands or transition metals and organic ligands is summarized. Not only the structural features and main applications but also the challenges and the focus of future research on POV-based materials are discussed.